'I don't know if I'm making the right decision': French mothers and HPV vaccination in a context of controversy. (17th February 2017) - Ward, Jeremy K.; Crépin, Laure; Bauquier, Charlotte; Vergelys, Chantal; Bocquier, Aurélie; Verger, Pierre; Peretti-Watel, Patrick
Abstract : Human papillomavirus (HPV) vaccination coverage in France has fallen substantially since 2010 and the onset of a media controversy on the subject of its safety and efficacy. In this article we examine how and why mothers agree or do not agree to HPV vaccination for their daughters. We draw on data from a survey of French mothers of girls within the HPV vaccination target population (11–14 years old). We used semi-structured interviews to examine their perceptions of this relatively new vaccine and how such perceptions were shaped by their past experiences of vaccines and health in general. We also talked to them about their sources of information, their level of trust in these sources, and how their perception of risk changed as they accessed different and often contradictory information. We found that mothers' fears of side effects and of 'new' vaccines was one of the main reason why they either refused to get their daughters vaccinated or hesitated. Mothers told us that they consulted several different sources, tended to trust their doctors most, but still questioned their recommendations. Although they presented the media and the Internet as untrustworthy, the information from those sources, whether gathered proactively or in passing, significantly influenced their decisions by introducing doubt or by prompting more information-seeking. In this article we show the dynamic nature of this decision-making process and we found that a substantial number of the mothers in our study said that they had been advised by at least one of their doctors not to have their daughter vaccinated.